DJ-1, a peten inhibitor, is a positive regulator of cancer cell motility. (c2014) - Yassine, Rawan M. (2016)
DJ-1 is a 20-KDa protein that was first identified as an oncogene product responsible for a subset of familial Parkinson’s disease; hence its name PARK 7. Previous studies showed that DJ-1 negatively regulated the tumor suppressor gene PTEN expression; thus promoting the phosphorylation of the PI3K/Akt signaling pathway, and activating cell proliferation and transformation. Therefore, DJ-1 can be used as an indication of cancer metastasis and can be a potential therapeutic target. However, the localization, detailed mechanism and the role of DJ-1 in cellular motility are still not fully understood. Therefore, our study showed that DJ-1, at normal cellular condition, is present in the nucleus, mitochondria, golgi apparatus and plasma membrane of astrocytoma (SF268) cells. Upon its stimulation with EGF, DJ-1 localize outside the nucleus, leading to an increase in cellular motility in lung, brain, and breast cancer cells by activating the PI3K pathway. We also showed that this activation is carried out by inhibiting PTEN and thus regulating the RhoGTPases mainly Rac which is known to be involved in cellular motility.